The emergence of cereal fungal diseases and the incidence of leaf spot diseases in Finland - Jalli, Marja; Laitinen, Pauliina; Latvala, Satu (Agricultural and Food Science, 2011)
Fungal plant pathogens causing cereal diseases in Finland have been studied by a literature survey, and a field survey of cereal leaf spot diseases conducted in 2009. Fifty-seven cereal fungal diseases have been identified in Finland. The first available references on different cereal fungal pathogens were published in 1868 and the most recent reports are on the emergence of Ramularia collo-cygni and Fusarium langsethiae in 2001. The incidence of cereal leaf spot diseases has increased during the last 40 years. Based on the field survey done in 2009 in Finland, Pyrenophora teres was present in 86%, Cochliobolus sativus in 90% and Rhynchosporium secalis in 52% of the investigated barley fields. Mycosphaerella graminicola was identified for the first time in Finnish spring wheat fields, being present in 6% of the studied fields. Stagonospora nodorum was present in 98% and Pyrenophora tritici-repentis in 94% of spring wheat fields. Oat fields had the fewest fungal diseases. Pyrenophora chaetomioides was present in 63% and Cochliobolus sativus in 25% of the oat fields studied.;